2018
DOI: 10.1016/j.bbr.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

No effect of sex and estrous cycle on the fear potentiated startle response in rats

Abstract: The prevalence of anxiety disorders is higher in women than in men. Yet preclinical studies on anxiety are mostly performed in male subjects. This may have limited our understanding of mechanisms contributing to anxiety disorders. Since fear conditioning is considered an important factor in the etiology of anxiety disorders, the present study aimed to investigate the effect of sex and estrous cycle on conditioned fear and the anxiolytic effect of benzodiazepines in rats. We measured the fear-potentiated startl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 94 publications
3
17
0
1
Order By: Relevance
“…In tests using conditioned fear paradigms (FPS and conditioned fear to context), females as a group responded in the same way as males, and we were unable to detect any difference in responsiveness at different stages of the oestrous cycle. Our findings are in agreement with previous reports of similar experiments using Wistar and Lewis rats (Cossio et al, 2016; Maeng et al, 2015; Pryce et al, 1999; Zhao et al, 2018). On the other hand, they contrast with results of other studies using these tests in which males were reported to be more responsive than females (de Jongh et al, 2005; Gresack et al, 2009; Maren et al, 1994; Pettersson et al, 2016).…”
Section: Discussionsupporting
confidence: 94%
“…In tests using conditioned fear paradigms (FPS and conditioned fear to context), females as a group responded in the same way as males, and we were unable to detect any difference in responsiveness at different stages of the oestrous cycle. Our findings are in agreement with previous reports of similar experiments using Wistar and Lewis rats (Cossio et al, 2016; Maeng et al, 2015; Pryce et al, 1999; Zhao et al, 2018). On the other hand, they contrast with results of other studies using these tests in which males were reported to be more responsive than females (de Jongh et al, 2005; Gresack et al, 2009; Maren et al, 1994; Pettersson et al, 2016).…”
Section: Discussionsupporting
confidence: 94%
“…Although the literature contains many conflicting reports on estradiol’s effects on fear- and anxiety-related behavior, our finding in LAP1 females is consistent with at least one report indicating anxiolytic effects of estrogen replacement on contextual fear behavior in rats [76]. Other studies in cycling rats have not found effects of estrous cycle on the expression of FPS [77,78,79]. These findings highlight the importance of monitoring the estrous cycle and, if possible, measuring estradiol when testing both males and females in fear-conditioning studies.…”
Section: Discussionsupporting
confidence: 90%
“…Sample size calculations for both experiments were based on previous studies in our laboratory (Bijlsma et al 2015). A methodological study from our lab showed that male and female rats do not differ in their fear-potentiated startle response (Zhao et al 2018a). The present study was therefore only performed in male rats to reduce the total number of animals needed.…”
Section: Methodsmentioning
confidence: 99%